Symbols of Protestant Culture in Northern Lithuania: Stove Tiles Featuring the Image of Sibylle von Kleve - Paškonytė, Jūratė (Acta humanitarica academiae Saulensis, 2025)
The subject of the article is the stove tiles featuring the portrait of Sibylle von Kleve. In order to conduct a comprehensive study, four tasks were set: (1) To identify the patrons (owners) of the stoves where Reformation tiles with the image of Sibylle were used, and to describe their beliefs, political, religious, and confessional views; (2) Based on the nearby found tiles and their overall analysis, to highlight the context in which these findings were discovered; (3) To determine the authorship of the prototype for the stove tiles featuring Sibylle von Kleve’s image; (4) To analyse whether these tiles reflect general European trends in Reformation stove tiles or if they have distinctive local characteristics. The topic is revealed using information from sources and scholarly literature, as well as the tile and iconographic material collected by the author between 2022 and 2024. In addition to the iconographic analysis, the research also relies on comparative analysis.The stove tiles discovered during archaeological research, depicting her image, are considered as the symbols of Protestant culture. This is especially confirmed by the fact that such tiles were found and identified in Northern Lithuania, in Biržai and Kražiai estates, where the rulers were the members of the Radziwiłł family. The prototype for the relief design of the tiles was based on woodcuts by Hans Brosamer (for Biržai tiles, no counterparts were found) and Lucas Cranach the Elder (for Kražiai tiles). The image by the latter engraver was used in stove tile decoration at Bauska Castle (Livonian Confederation, from 1561 – Duchy of Courland and Semigallia, now Latvia), Sparrenburg Castle (Holy Roman Empire’s German territories, now Germany), Turku Castle (Kingdom of Sweden, now Finland), the building at 4 University Street in Vilnius (Grand Duchy of Lithuania), after 1569 – The Polish-Lithuanian Commonwealth, now Lithuania), the Artus Court in Gdansk (before 1569 – Kingdom of Poland, after 1569 – Polish-Lithuanian Commonwealth, now Gdansk, Poland), the city of Opočno (before 1569 – Kingdom of Poland, after 1569 – Polish-Lithuanian Commonwealth, now Poland), and Česká Lípa (Kingdom of Bohemia, part of the Holy Roman Empire, now Czech Republic).
Keywords: Sibylle von Kleve; stove tiles; Biržai Manor; Kražiai Manor; Radziwiłłs; Reformation